Nursing management of a patient with delayed skin necrosis caused by extravasation of calcium chloride (1例氯化钙外渗致迟发性皮肤局部坏死的护理) - CHEN Mingrui (陈明锐); GAO Xiaohong (高小红); CHEN Meirong (陈美容) (Association of Integrative Nursing, 2022)
This paper summarized nursing measures for a patient with delayed skin necrosis caused by extravasation of calcium chloride. The patient was given magnesium sulfate wet dressing and external application of Povidone Iodine ointment. A scientific method of dressing change was adopted based on different stage of wound healing. Comprehensive nursing and health education interventions were carried out during the treatment. (总结1例氯化钙外周输液出现外渗导致迟发性皮肤局部坏死的护理经验。采取硫酸镁湿敷和聚维酮碘软膏外涂, 根据创面不同时期选择合适的敷料, 规律换药, 同时对患者进行全面护理, 加强健康宣教。)